Gold(III)-Catalyzed Intramolecular Furanylation and Cyclopropanation of Acyclic Conjugated Enynones - Oh, Chang Ho; Piao, Lanhua; Kim, Ji Hee (Synthesis, 2013)
We have developed an efficient cascade gold-catalyzed furanylation–cyclopropanation of acyclic (E)-deca-2,9-dien-4-yn-1-ones and an (E)-undeca-2,10-dien-4-yn-1-one to give 1-(2-furyl)bicyclo[3.1.0]hexanes and a 1-(2-furyl)bicyclo[4.1.0]heptane, respectively. This requires a configurational change from the E-isomer to the Z-isomer prior to furan formation. The intermediate was proposed to be a gold–carbene, which would undergo cyclopropanation to furnish the product.
Keywords: cyclization; gold catalyst; furanylation; cyclopropanation; enynone